Empowering nonmedical personnel to detect scabies in endemic area using DeSkab instrument: A diagnostic study - Widaty, Sandra; Kekalih, Aria; Friska, Dewi; Bramono, Kusmarinah; Sari, Siti Maulidya; Darmawan, Irene; Sujudi, Yufanti; Hartanto, David Dwiadiputra; Kartika, Emiliana; Oktavia, Nikken Rima (UI Scholars Hub, 2024)
Background: Scabies has been added to World Health Organization (WHO) list of neglected tropical disease in 2017. Various methods have been developed to control scabies in highly prevalent communities. In this study we conducted a diagnostic study to evaluate the performance of scabies detection by trained nonmedical personnel (NMP) using Deteksi Skabies (Deskab) instrument which has been validated for NMP. Methods: Eight NMPs in a boarding school were trained to detect scabies using DeSkab instrument. The NMPs diagnosis were compared to diagnosis of 10 medical doctors. The study was conducted in a religion-affiliated boarding school in West Java, Indonesia. Both examiners consecutively assessed boarding school students using DeSkab instrument and were blinded to each other findings. Results: Among 140 participants included in this study, scabies was confirmed by medical doctors in 60 participants. Diagnostic accuracy of NMPs examination is 72.14% [95% confidence interval (CI) 64.2-78.9], with sensitivity and specificity 67.42% (95% CI 57.13-76.26), and 80.32% (95% CI 67.54-88.98) respectively. The inter-rater agreement (Cohen’s kappa) for diagnosing scabies is 0.44. Conclusion: NMPs can be trained to detect scabies in their community with acceptable accuracy. Improving training are recommended to further improve the diagnosis skills and maintaining sustainable detection program.